Eligibility Criteria for Ferric Carboxymaltose in Women with Iron Deficiency in Obstetrics: An Algerian Expert Consensus - Rachida Aouameur; Hafida Bendaoud; Ouafa Guellati; Amel Dammene-Debbih; Manar Lahmar; Nacera Benmouhoub; Zahra Farah; Hichem Makhloufi; Issam Frigaa; Fadela Madaci; Lamine Mahi (Journal of Applied Hematology)
BACKGROUND: Iron deficiency (ID) and ID anemia (IDA) are widespread health issues affecting a significant number of women in Algeria, particularly during pregnancy. With a lack of clear, localized guidelines for managing ID and IDA in Algeria, the need for a consensus on the eligibility criteria for ferric carboxymaltose (FCM) usage in obstetrics was recognized. AIMS AND OBJECTIVES: In this context, a national expert panel aimed to establish a consensus on the eligibility criteria for FCM as the optimal intravenous (IV) iron treatment for women with ID/IDA in obstetrics, based on shared experiences and insights. METHODS: The expert panel, comprising seven obstetricians and gynecologists, three anesthetists and intensive care specialists, and one hematologist, deliberated on the use of IV iron therapy, specifically FCM, in the field of obstetrics. RESULTS: The panel reached a consensus on serum ferritin cutoff levels, key diagnostic parameters for IDA, the role of C-reactive protein in IDA screening, and the need for harmonization with international guidelines. They also discussed the treatment of ID/IDA, including nutritional well-being, oral and IV iron therapy, and the indication of transfusion. Specific criteria for prescribing IV iron, especially FCM, to pregnant women were identified. CONCLUSION: This expert consensus represents a significant step toward improving the diagnosis and management of ID and IDA during pregnancy in Algeria. The recommendations emphasize the efficient and effective use of FCM as an IV treatment, enhancing the standard of care for obstetric patients.